High efficiency silicon nanohole/organic heterojunction hybrid solar cell - Hong, Lei (2014)
High efficiency hybrid solar cells are fabricated based on silicon with a nanohole (SiNH) structure and poly (3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS). The SiNH structure is fabricated using electroless chemical etching with silver catalyst, and the heterojunction is formed by spin coating of PEDOT on the SiNH. The hybrid cells are optimized by varying the hole depth, and a maximum power conversion efficiency of 8.3% is achieved with a hole depth of 1 μm. The SiNH hybrid solar cell exhibits a strong antireflection and light trapping property attributed to the sub-wavelength dimension of the SiNH structure.